Philippines Quarterly Update, January 2011 : Robust Growth, Stubborn Poverty - World Bank (World Bank, Manila, 2017)
Following a slowdown during the global financial crisis in 2009, the Philippine economy roared back in 2010, with Gross Domestic Product (GDP) growth rates not seen in over 30 years. On the demand side, private consumption, investment, and net exports were the main drivers of growth. On the supply side, industry and services propelled the economy. The external position continued to strengthen, thanks to a consistently strong current account and, more recently, by improvements in the capital and financial account. Dollar remittances grew progressively faster throughout 2010. Labor market conditions improved, but unemployment remains high, contributing to strong OFW deployment. Growth is expected to normalize around its potential output in 2011 as the technical and temporary factors that generated record growth in 2010 disappear. Among its first actions in office, the Aquino government carried out a comprehensive assessment of fiscal risks and published a Fiscal Risk Statement (FRS). Experience reveals that FRSs can yield important benefits, including lower and better, managed risks, improved policies, and lower financing costs. Historically, the Philippines have been exposed to considerable fiscal risks, in part reflecting important weaknesses in public financial management and resulting in large fiscal costs. While fiscal risks have abated, they still remain sizeable in the Philippines. To improve its risk management, the government is pursuing a program of institutional capacity building.